Rates of primary and secondary treatments for patients on active surveillance for localized prostate cancer—A population‐based cohort study - Rano Matta; Amanda E. Hird; Erind Dvorani; Refik Saskin; Gregory J. Nason; Girish Kulkarni; Ronald T. Kodama; Sender Herschorn; Robert K. Nam (Cancer Medicine)
Abstract Background The rate of primary and secondary treatment while on active surveillance (AS) for localized prostate cancer at the general population level is unknown. Our objective was to determine the patterns of secondary treatments after primary surgery or radiation for patients who undergo AS. Methods This was a population‐based retrospective cohort study of men aged 50‐80 years old in Ontario, Canada, between 2008 and 2016. We identified 26 742 patients with prostate cancer, a Gleason grade score ≤7, and an index prostate‐specific antigen ≤10 ng/mL. Patients were categorized as undergoing AS with or without delayed primary treatment (DT; treatment >6 months after diagnosis) versus immediate treatment (IT; treatment ≤6 months). Patients receiving DT and IT were propensity score matched and the rate of secondary treatment (surgery or radiation ± androgen deprivation treatment) was compared using Cox proportional hazards models. Results We identified 10 214 patients who underwent AS and 11 884 patients who underwent IT. Among patients undergoing AS, 3724 (36.5%) eventually underwent DT and among them, 406 (10.9%) underwent secondary treatment. The median time to DT was 1.2 years (IQR 0.5‐8.1 years). The relative rate of undergoing secondary treatment was similar in the DT vs IT group (HR 0.92; 95% CI: 0.79‐1.08). The risk of death in the DT group was higher compared to patients who did not undergo treatment (HR 1.23, 95% CI: 1.01‐1.49). Conclusions Among patients with localized prostate cancer on AS, one third undergo DT. The rate of secondary treatment was similar between the DT and IT groups. Patients in the DT group may experience a higher risk of mortality compared to those who remained on AS.